Some natural compounds and their analogues having potent anti- SARS-CoV-2 and anti-proteases activities as lead molecules in drug discovery for COVID-19 - Biswanath Dinda; Manikarna Dinda; Subhajit Dinda; Mithun Chakraborty (Elsevier, 2022)
Currently an emerging human pathogenic coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), caused coronavirus disease 2019 (COVID-19) that has posed a serious threat to public health worldwide. As it is a novel severe pneumonia-type viral disease, no effective therapeutic agents are available to treat this infection to date, emphasizing an urgent need for development of effective anti-SARS-CoV-2 agents. Based on screening in computational biology and biological in vitro assays, a good number of natural compounds and their synthetic analogues have been confirmed to possess target-specific inhibitory effects against the activity of host and viral proteases, namely, cathepsin-L, TMPRSS2, Sec61, Mpro (3CL-protease), RNA-dependent RNA protease (RdRp), helicase cap-binding proteases eEF1A, eIF4A, eIF4E, which play dominant roles in progression of infection and replication of SARS-CoV-2 virus in host cells. This review paper describes the potent antiviral activity and target-specific anti-proteases activity of some natural compounds and their synthetic analogues against SARS-CoV-2 infection. It will inspire the researchers to unleash their own creativity and to design potent and safe drugs to fight the current COVID-19 pandemic.